In vivo Visualization of M2 Macrophages in the Myocardium After Myocardial Infarction (MI) Using 68Ga-NOTA-Anti-MMR Nb: Targeting Mannose Receptor (MR, CD206) on M2 Macrophages - Varasteh, Zohreh; Braeuer, Miriam; Mohanta, Sarajo; Steinsiek, Anna-Lena; Habenicht, Andreas; Omidvari, Negar; Topping, Geoffrey J.; Rischpler, Christoph; Weber, Wolfgang A.; Sager, Hendrik B.; Raes, Geert; Hernot, Sophie; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction and objectives: Wound healing after myocardial infarction (MI) is a dynamic and complex multiple phase process, and a coordinated cellular response is required for proper scar formation. The current paradigm suggests that pro-inflammatory monocytes infiltrate the MI zone during the initial pro-inflammatory phase and differentiate into inflammatory macrophages, and then switch their phenotypes to anti-inflammatory during the reparative phase. Visualization of the reparative phase post-MI is of great interest because it may reveal delayed resolution of inflammation, which in turn predicts adverse cardiac remodeling. Imaging of anti-inflammatory macrophages may also be used to assess therapy approaches aiming to modulate the inflammatory response in order to limit MI size. Reparative macrophages can be distinguished from inflammatory macrophages by the surface marker mannose receptor (MR, CD206). In this study, we evaluated the feasibility of 68Ga-NOTA-anti-MMR Nb for imaging of MR on alternatively activated macrophages in murine MI models. Methods: Wildtype and MR-knockout mice and Wistar rats were subjected to MI via permanent ligation of the left coronary artery. Non-operated or sham-operated animals were used as controls. MR expression kinetics on cardiac macrophages was measured in mice using flow cytometry. In vivo˗PET/CT scans were performed 1 h after intravenous injection of 68Ga-NOTA-anti-MMR Nb. Mice and rats were euthanized and hearts harvested for ex vivo˗PET/MRI, autoradiography, and staining. As a non-targeting negative control, 68Ga-NOTA-BCII10 was used. Results: In vivo˗PET/CT scans showed focal radioactivity signals in the infarcted myocardium for 68Ga-NOTA-anti-MMR Nb, which were confirmed by ex vivo˗PET/MRI scans. In autoradiography images, augmented uptake of the tracer was observed in infarcts, as verified by the histochemistry analysis. Immunofluorescence staining demonstrated the presence and co-localization of CD206- and CD68-positive cells, in accordance to infarct zone. No in vivo or ex vivo signal was observed in the animals injected with control Nb or in the sham-operated animals. 68Ga-NOTA-anti-MMR Nb uptake in the infarcts of MR-knockout mice was negligibly low, confirming the specificity of 68Ga-NOTA-anti-MMR Nb to MR. Conclusions: This exploratory study highlights the potential of 68Ga-NOTA-anti-MMR Nb to image MR-positive macrophages that are known to play a pivotal role in wound healing that follows acute MI.